2021
DOI: 10.4322/acr.2021.302
|View full text |Cite
|
Sign up to set email alerts
|

Maxillary dentigerous cyst showing squamous odontogenic tumor-like proliferation: surgical approach and literature review

Abstract: Squamous odontogenic tumor (SOT) is a rare benign neoplasm of the jaw that likely arises from remnants of the dental lamina. It is a slow-growing lesion, with a radiolucent appearance in the central variant. Microscopically, SOT shows islands of squamous epithelium supported by fibrous stroma. In rare cases, squamous odontogenic tumor-like proliferation (SOT-LP) can be observed arising from odontogenic cysts (SOT-LPOC). Herein, we describe the case of a 42-year-old man who presented with discreet bleeding in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…A review by Chrnovic and Gomez (2018) analyzed cases of proliferation of SOT and squamous odontogenic tumor-like proliferation in odontogenic cysts (SOT-LPOC) thus concluding that they are different clinicopathological conditions since SOT showed a more aggressive growth pattern: the former had unilocular or multilocular aspect and was associated with cortical bone perforation in 62 % of central lesions and tooth displacement while the latter showed no signs of bone erosion or root resorption and were most associated with radicular and dentigerous cysts, as it appeared most of the times as an unilocular lesion. (11) Also Barbeiro et al (2021) described a case of maxillary dentigerous cyst involving tooth 18 which showed squamous odontogenic tumor like proliferation: their group managed to treat it by enucleation of the lesion and involved tooth and obtained complete healing and no recurrence after 3 year follow-up. Considering all clinical differences between the two kind of lesions it is not possible to assert that SOT is the natural progression of SOT-LPOC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A review by Chrnovic and Gomez (2018) analyzed cases of proliferation of SOT and squamous odontogenic tumor-like proliferation in odontogenic cysts (SOT-LPOC) thus concluding that they are different clinicopathological conditions since SOT showed a more aggressive growth pattern: the former had unilocular or multilocular aspect and was associated with cortical bone perforation in 62 % of central lesions and tooth displacement while the latter showed no signs of bone erosion or root resorption and were most associated with radicular and dentigerous cysts, as it appeared most of the times as an unilocular lesion. (11) Also Barbeiro et al (2021) described a case of maxillary dentigerous cyst involving tooth 18 which showed squamous odontogenic tumor like proliferation: their group managed to treat it by enucleation of the lesion and involved tooth and obtained complete healing and no recurrence after 3 year follow-up. Considering all clinical differences between the two kind of lesions it is not possible to assert that SOT is the natural progression of SOT-LPOC.…”
Section: Discussionmentioning
confidence: 99%
“…Considering all clinical differences between the two kind of lesions it is not possible to assert that SOT is the natural progression of SOT-LPOC. (12) The election treatment modality is conservative enucleation with curettage; other cases reported in literature received a more aggressive treatment consisting on en bloc resection, hemimaxillectomy or radical alveolectomy. Moreover, it is suggested to treat multilocular, multifocal and/or recurrent lesions involving maxilla, which is known to be more porous than mandible, with an extensive intervention.…”
Section: Discussionmentioning
confidence: 99%